Influencing eating choices, manipulating emotions, & the influencer: an ethnography - Mukherjee Somdatta (Online Media and Global Communication)
This study inspects that our eating choice depends on our economic condition, availability of the raw materials and the food we wish to consume etc. Then, it examines how that choice is manipulated by influencers on social media and food-related contents on social media influence our thought process regarding food intake.